2021
DOI: 10.1038/s41541-021-00281-z
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia pseudomallei OMVs derived from infection mimicking conditions elicit similar protection to a live-attenuated vaccine

Abstract: Burkholderia pseudomallei is a Gram-negative, facultative intracellular bacillus that causes the disease melioidosis. B. pseudomallei expresses a number of proteins that contribute to its intracellular survival in the mammalian host. We previously demonstrated that immunization with OMVs derived from B. pseudomallei grown in nutrient-rich media protects mice against lethal disease. Here, we evaluated if OMVs derived from B. pseudomallei grown under macrophage-mimicking growth conditions could be enriched with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…The addition of the OMVs can mimic a live bacterium to stimulate the immune response [ 14 ]. Indeed, B. pseudomallei OMVs have recently been shown to behave like and elicit similar protection to a live-attenuated vaccine [ 37 ]. Here, we hypothesized that the addition of B. pseudomallei OMVs to HKST would boost the immune response to Salmonella alone and confer protection against challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of the OMVs can mimic a live bacterium to stimulate the immune response [ 14 ]. Indeed, B. pseudomallei OMVs have recently been shown to behave like and elicit similar protection to a live-attenuated vaccine [ 37 ]. Here, we hypothesized that the addition of B. pseudomallei OMVs to HKST would boost the immune response to Salmonella alone and confer protection against challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of OMVs to other mucosal surfaces would be beneficial in defining their adjuvant role and whether they are capable of inducing both humoral and cellular immunity at any site or if this phenomenon is gut specific. In this study, we used B. pseudomallei OMVs based on previous literature showing their safety and efficacy both as a vaccine and an adjuvant [ 13 , 14 , 37 ]. Overall, this study highlights the first time that B. pseudomallei OMVs have been employed to adjuvant an oral vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we demonstrated that OMVs could be selectively-enriched with intracellular stage-specific proteins, leading to robust humoral and cellular immune responses that exceeded those induced by a live-attenuated strain [14]. Notably, OMVs possessed inherent adjuvanticity and conferred vaccine protection in mice and NHPs without a requirement for exogenous adjuvant.…”
Section: Introductionmentioning
confidence: 95%
“…Preclinical and clinical studies conducted with GMMA-based vaccines have addressed humoral responses but poorly the cellular response ( Figure 1C ). Baker and co-authors demonstrated that OMV could induce robust cellular immune responses that exceeded those induced by a live-attenuated strain ( 65 ).…”
Section: Gaps On Understanding the Basis Of Gmma Immunogenicity And Potential Challengesmentioning
confidence: 99%